INTERNAL CONTROL SYSTEM, UTILIZATION OF ACCOUNTING INFORMATION TECHNOLOGY, ON VILLAGE FUND MANAGEMENT ACCOUNTABILITY - Yenty Astari Dewi; Nasfi Nasfi; Mai Yuliza (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
The government prioritizes Villages in development, providing funds for Villages which are taken directly from the State Revenue and Expenditure Budget to be managed by the Village independently. The research objective was to determine the effect of the influence of the internal control system, the use of accounting information technology, and the competence of the Nagari apparatus on the accountability of village fund management. This type of quantitative research, a sample of 20 Nagari in Agam District, as many as 80 respondents, using convenience sampling techniques, the data in this study were collected using a questionnaire and analyzed using multiple regression analysis. The results of the research F test results F value 31.750> F table 2.74, 95% confidence level and significant 0.05, Fcount > F table conclusion that there is an effect of independent variables (X1, X2 and X3) on the dependent variable (Y) simultaneously. A separate t-test test found that the internal control system variable (X1) did not have a significant effect on the accountability of Village Fund management, the variable use of accounting information technology and the competence of Nagari officials (X2 and X3) had a significant effect on the accountability of Village Fund management. Keywords: Internal Control System, Utilization of Accounting Information Technology, Nagari Apparatus Competence, Accountability, Village Fund.